The Declaration of Helsinki in bioethics literature since the last revision in 2013 - Ehni, Hans‐Jörg; Wiesing, Urban (Bioethics, 2024)
The World Medical Association has announced that a new revision process of the Declaration of Helsinki has been started. This article will identify the criticisms that have been made in the bioethics literature, particularly since the last revision. In addition, criticisms are discussed that were made in the literature even before the last revision and have not fallen silent. The plausibility of the recommendation for a change in the Declaration of Helsinki is examined.